TÄrikh TaÊ¿lÄ«m Ê¿Ilmi al-Naá¸¥wi min al-Ê¿Aá¹£ri al-KalÄsÄ«kiy ila al-Ê¿Aá¹£ri al-á¸¤adÄ«th fi al-MujtamaÊ¿ 5.0 - Primadana, Ramadhan Jabal; Achmad Fahmi, Bagus Maulana; Muttaqin, Zainal (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2023)
This article aims to provide historical information on the development of nahwu science from classical times at the beginning of the emergence of Islam to modern times in the 5.0 era. The 5.0 era refers to the development of information and communication technology that changes the learning paradigm significantly. This research uses historical analysis methods and literature studies to collect data about the history of science and its development until the modern era. The results of this research are expected to provide in-depth insight into the history of science and its development accompanied by examples of learning systems and methods such as the Tanya Zaid chatbot system, Arruz Applications, and electrical methods in learning the era of society 5.0. This will help develop more effective and relevant learning methods to meet the increasingly complex learning needs of science and technology that continues to evolve. ØªÙ‡Ø¯Ù Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„Ø© Ù„ØªÙ‚Ø¯ÙŠÙ… Ø§Ù„Ù…Ø¹Ù„ÙˆÙ…Ø§Øª Ø§Ù„ØªØ§Ø±ÙŠØ®ÙŠØ© Ø¹Ù† ØªØ·ÙˆØ± Ø¹Ù„Ù… Ø§Ù„Ù†ØÙˆÂ Ù…Ù† Ø§Ù„Ø¹ØµÙˆØ± Ø§Ù„ÙƒÙ„Ø§Ø³ÙŠÙƒÙŠØ© ÙÙŠ Ø¨Ø¯Ø§ÙŠØ© Ø¸Ù‡Ùˆ Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ø¥Ù„Ù‰ Ø§Ù„Ø¹ØµØ± Ø§Ù„ØØ¯ÙŠØ« ÙÙŠ Ø¹ØµØ± Ø§Ù„Ø®Ø§Ù…Ø³Ø©. ÙŠØ´ÙŠØ± Ø¹ØµØ± 5.0 Ø¥Ù„Ù‰ ØªØ·ÙˆÙŠØ± ØªÙƒÙ†ÙˆÙ„ÙˆØ¬ÙŠØ§ Ø§Ù„Ù…Ø¹Ù„ÙˆÙ…Ø§Øª ÙˆØ§Ù„Ø§ØªØµØ§Ù„Ø§Øª Ø§Ù„ØªÙŠ ØªØºÙŠØ± Ù†Ù…ÙˆØ°Ø¬ Ø§Ù„ØªØ¹Ù„Ù… Ø¨Ø´ÙƒÙ„ ÙƒØ¨ÙŠØ±. ÙŠØ³ØªØ®Ø¯Ù… Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø£Ø³Ø§Ù„ÙŠØ¨ Ø§Ù„ØªØÙ„ÙŠÙ„ Ø§Ù„ØªØ§Ø±ÙŠØ®ÙŠ ÙˆØ¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø£Ø¯Ø¨ÙŠØ§Øª Ù„Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ØÙˆÙ„ ØªØ§Ø±ÙŠØ® Ø§Ù„Ø¹Ù„Ù… ÙˆØªØ·ÙˆØ±Ù‡ ØØªÙ‰ Ø§Ù„Ø¹ØµØ± Ø§Ù„ØØ¯ÙŠØ«. ÙˆÙ†ØªØ§Ø¦Ø¬ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù†Ø¸Ø±Ø© Ù…ØªØ¹Ù…Ù‚Ø© ÙÙŠ ØªØ§Ø±ÙŠØ® Ø§Ù„Ø¹Ù„ÙˆÙ… ÙˆØªØ·ÙˆØ±Ù‡Ø§ Ù…Ø¹ Ø£Ù…Ø«Ù„Ø© Ø§Ù„Ø£Ù†Ø¸Ù…Ø© ÙˆØ£Ø³Ø§Ù„ÙŠØ¨ Ø§Ù„ØªØ¹Ù„Ù… Ù…Ø«Ù„ Ù†Ø¸Ø§Ù… Ø±ÙˆØ¨ÙˆØªØ§Øª Ø§Ù„Ø¯Ø±Ø¯Ø´Ø© Ø¥Ø³Ø£Ù„ Ø²ÙŠØ¯ ÙˆØªØ·Ø¨ÙŠÙ‚Ø§Øª Ø£Ø±ÙˆØ² ÙˆØ§Ù„Ø£Ø³Ø§Ù„ÙŠØ¨ Ø§Ù„ÙƒÙ‡Ø±Ø¨Ø§Ø¦ÙŠØ© ÙÙŠ ØªØ¹Ù„Ù… Ø¹ØµØ± Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ 5.0. ÙˆØ³ÙŠØ³Ø§Ø¹Ø¯ Ø°Ù„Ùƒ Ø¹Ù„Ù‰ ØªØ·ÙˆÙŠØ± Ø·Ø±ÙŠÙ‚Ø§Øª Ø§Ù„ØªØ¹Ù„Ù…ÙŠØ© Ø£ÙƒØ«Ø± ÙØ¹Ø§Ù„ÙŠØ© ÙˆÙ…Ù„Ø§Ø¡Ù…Ø© Ù„ØªÙ„Ø¨ÙŠØ© Ø§ØØªÙŠØ§Ø¬Ø§Øª Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù…ØªØ²Ø§ÙŠØ¯Ø© Ø§Ù„ØªØ¹Ù‚ÙŠØ¯ Ù„Ù„Ø¹Ù„ÙˆÙ… ÙˆØ§Ù„ØªÙƒÙ†ÙˆÙ„ÙˆØ¬ÙŠØ§ Ø§Ù„ØªÙŠ ØªØ³ØªÙ…Ø± ÙÙŠ Ø§Ù„ØªØ·ÙˆØ±.